Функции отделов кишечника акароидных клещей (Acaroidea) - Акимов, И.А. (Вестник зоологии, 1980)
Functions of the digestive system were studied by means of vital stains, pH indicators and light microscopy in special microcells. Formation of food balls from mucus, cell fragments and food pieces was observed in representatives of 15 genera from Acaridae and Glycyphagidae families. These balls were found to be surrounded by a peritrophic membrane and to move through the gut sections with stoppages. The influence of different factors on these processes, including concentration of some sugars, osmotic pressure and presence of small hard food pieces is discussed. The pH concentration in the gut sections is found to be constant. The digestive process in food balls under peritrophic membrane in the lumen of colon and localization of protein hydrolysis are demonstrated.